Seroprevalence of Hepatitis B Virus Co-Infection with Salmonella typhi in Wukari North-East Nigeria - Brown, Samuel Tamunoiyowuna Cockeye; Onyemaechi, Eze Emmanuel; Mohammed, Ikrimah Usman; Yahaya, Tanko Saadatu (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
Hepatitis B virus (HBV) and typhoid fever remain significant public health concerns, particularly in resource-limited settings where sanitation and healthcare infrastructure are inadequate. This study investigated the prevalence of HBV, Salmonella typhi, and their co-infection among febrile patients attending the General Outpatient Department (GOPD) of Federal University Teaching Hospital, Wukari, Taraba State, Nigeria. A total of 50 patients aged 15–65 years were recruited, and blood samples were analyzed using serological assays for HBV and Widal tests for Salmonella typhi detection. The study found an overall HBV prevalence of 30%, with males (37%) having a higher prevalence than females (21.7%). The prevalence of Salmonella typhi was 44%, with females (52.2%) showing a higher infection rate than males (37%). The co-infection rate of HBV and typhoid was 12%, with males (18.5%) exhibiting a higher burden than females (4.3%). The highest HBV prevalence was observed in individuals aged 31–40 years (34.7%), while typhoid was most prevalent in the 20–30 years (71.4%) and 41–50 years (70%) age groups. Co-infection was most common in the 31–40 years (21.7%) group. The findings suggest that gender, age, and exposure to risk factors such as poor hygiene and unsafe practices contribute to the high prevalence of these infections. The study underscores the need for enhanced public health interventions, including vaccination, improved sanitation, health education, and regular screening programs to mitigate the spread of HBV and typhoid fever.